The Improvement of Students' Creative and Collaborative Thinking Skills by Applying STEAM-Integrated Project-Based Learning - Achmad Basari Eko Wahyudi; Moh Salimi; Ratna Hidayah; Hasan Zainnuri; Laksmi Evasufi Widi Fajari (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2024)
This research introduced a new method by integrating STEAM-based project learning to effectively enhance students' creative and collaborative thinking skills, which has not been widely explored in the educational context. The subjects were 14 students consisting of 8 male students and 6 female fifth grade students who were selected using purposive sampling techniques. The type of research used Classroom Action Research. Data collection was carried out by interviews, observations and tests. The data analysis techniques used qualitative and quantitative. The study results showed that The average creative thinking skill of students was increase; the average collaborative thinking skill of students was increase; and learning outcomes also increased. The the result showed that STEAM integrated project-based learning can improve creative and collaborative thinking skills as well as students' social science learning outcomes. The research also contributed by showing that the implementation of STEAM-integrated project-based learning effectively enhances students' creative and collaborative thinking skills, providing a robust framework for educators to foster innovation, teamwork, and problem-solving abilities in the classroom, ultimately preparing students for complex real-world challenges.